Enhancing Job Satisfaction through Career Development and Organizational Climate: A Study on Non-ASN Employees in Kolaka - Anhar, Musyrifah; Kartomo, Kartomo; Rundu Wonua, Almansyah (SEAN Institute, 2025)
This study investigates the influence of career development and organizational climate on job satisfaction among non-permanent (non-ASN) employees at the Secretariat Office of the Regional People's Representative Council (DPRD) in Kolaka. Human resources are critical to organizational success, and job satisfaction plays a vital role in enhancing employee motivation and performance. Drawing from a quantitative explanatory research design, this study utilized a census sampling method involving 50 non-ASN employees, with data collected through structured questionnaires, interviews, documentation, and observation. The data were analyzed using SPSS 26.0 for instrument validity and reliability testing, and SmartPLS 3.0 for Structural Equation Modeling (SEM) to evaluate causal relationships. The findings reveal that both career development and organizational climate have a positive and significant effect on job satisfaction. Employees emphasized the importance of fair promotion opportunities, leadership support, and structural clarity in shaping their job satisfaction. However, the results also highlight a critical challenge: wage disparities and employment instability among non-ASN staff significantly undermine satisfaction levels. These findings suggest that while organizational and developmental factors are important, financial fairness and job security must be prioritized to sustain motivation and commitment. The study offers valuable implications for public sector policy, recommending an integrated approach that combines structural improvements, career growth initiatives, and equitable compensation to enhance employee satisfaction and organizational effectiveness.